Studies on the interactions between the Romans and aquatic environments - Silva, Guilherme de Aquino (Romanitas - Revista de Estudos Grecolatinos, 2026)
Review of: TIBBS, A.; CAMPBELL, P. B. (ed.). Rivers and waterways in the Roman World: empire of water. Oxon: Routledge, 2024. 273 p.